Comparison of carbonic anhydrase-IX-targeted trifunctional radioligands between linear- and branched-chain arrangements - Nakashima, Kazuma; Ichinose, Takayoshi; Watanabe, Hiroyuki; Ono, Masahiro (Frontiers in Nuclear Medicine, 2025)
BackgroundCarbonic anhydrase-IX (CA-IX) is overexpressed in tumors due to hypoxic conditions and considered an attractive biomarker for tumor-targeting radioligands. The introduction of an albumin binder (ALB) to radioligands can delay their renal clearance, resulting in increased radioactivity delivered to tumors and decreased renal uptake of radioligands. In this study, we designed novel CA-IX-targeted trifunctional radioligands consisting of imidazothiadiazole sulfonamide (IS) as a CA-IX-targeted ligand, DOTA as a chelator with four free carboxylic groups, and lysine-conjugated 4-(p-iodophenyl)butyric acid (Lys-IPBA) as ALB, with IS-[111In]In-DOTADG-ALB in a linear-chain arrangement and [111In]In-DOTAGA-ALB-IS in a branched-chain arrangement. Fundamental properties of IS-[111In]In-DOTADG-ALB and [111In]In-DOTAGA-ALB-IS were evaluated by in vitro and in vivo assays.MethodsIS-DOTADG-ALB and DOTAGA-ALB-IS were synthesized and radiolabeled with [111In]InCl3. The stability of IS-[111In]In-DOTADG-ALB and [111In]In-DOTAGA-ALB-IS was evaluated by HPLC analysis after incubation in murine plasma. A cell saturation binding assay using CA-IX-positive HT-29 cells and albumin-binding assay were performed for IS-[111In]In-DOTADG-ALB and [111In]In-DOTAGA-ALB-IS to evaluate their capacity to bind CA-IX and albumin. Biodistribution assays of IS-[111In]In-DOTADG-ALB and [111In]In-DOTAGA-ALB-IS were performed using HT-29 tumor-bearing mice to evaluate their pharmacokinetics.ResultsIS-[111In]In-DOTADG-ALB and [111In]In-DOTAGA-ALB-IS were successfully synthesized by ligand substitution reaction from their corresponding precursors. IS-[111In]In-DOTADG-ALB and [111In]In-DOTAGA-ALB-IS exhibited similar stabilities in murine plasma and affinities to CA-IX, although the affinities to albumin were higher for [111In]In-DOTAGA-ALB-IS compared with IS-[111In]In-DOTADG-ALB. In the biodistribution assays, [111In]In-DOTAGA-ALB-IS showed higher blood retention and tumor accumulation and lower renal uptake than IS-[111In]In-DOTADG-ALB, reflecting their albumin-binding affinities.ConclusionThese data suggest that the branched-chain arrangement of DOTAGA-ALB-IS may be useful for the design of CA-IX-targeted radioligands consisting of an IS ligand, DOTA, and Lys-IPBA.